Unconventional livestock: classification and potential uses (2003)
Although unconventional livestock species are reservoirs of valuable genetic resources, and many have traditionally been used as resources of animal protein, fibre, transport and draught power, very little has been done to develop their commercial exploitation. This paper attempts to classify unconventional livestock according to their size, ecological affinity and economic importance. It also discusses their use in systems with limited production resources, their complementary until conventional livestock, and the potential of multipurpose species for specialized production of products vital for the sustenance of the human population.